Interview performance[videorecording] (VEA, 2006)
You only get one chance to make first impression. A successful job interview can be a key moment in a person's life : preparation, presentation, coping with the experince, and follow up are all crucial factors in the process. In this program we offer helpful hints on how to cope with nerves, asking appropriate questions, body language, and ensuring the interview ends on a positive note. We also get invaluable advice from carrers consultatns and trade union representatives. Interview performance will help students understand that interviews are something we all get better at. Success is usually just around the corner.